Real exchange rate effect on economic growth: Comparison of fundamental equilibrium exchange rate and Balassa-Samuelson based Rodrik approach - Mehdi Seraj; Cagay Coskuner (Journal of Applied Economics, 2021)
This study reproduces the work of Dani Rodrik on real exchange rate undervaluation and economic growth for 93 countries over the period 1990-2018. While the empirical literature on the dynamics between the real exchange rate11 It is a measure of the bilateral real exchange rate with respect to the US dollar. and economic growth is relatively comprehensive, little has been done to compare these dynamics within economies using the Balassa-Samuelson-based Rodrik approach (BS) and the fundamental equilibrium exchange rate model (FEER). This research, to the best of the authors' knowledge, is one of the first to compare the fundamental equilibrium exchange rate model and Balassa-Samuelson-based Rodrik approach and use dynamic estimation on the Rodrik approach. The findings of the study support Rodrik's conclusion that undervaluation has a significant impact on economic growth, although the results of FEER are more significant than those of BS. Furthermore, the first lag of undervaluation has a significant effect on economic growth.
Keywords: 330; Balassa-Samuelson effect; Economic growth; exchange rate undervaluation; fundamental equilibrium exchange rate model; Rodrik model